Association Between Ambient Fine Particulate Matter and Physical Functioning in Middle-Aged and Older Chinese Adults: A Nationwide Longitudinal Study. Issue 5 (15th December 2021) - Wang, Huiyu; Liu, Hengyi; Guo, Fuyu; Li, Jiajianghui; Li, Pengfei; Guan, Tianjia; Yao, Yao; Lv, Xiaozhen; Xue, Tao
Abstract: Background: Exposure to air pollution is associated with several chronic diseases and subclinical processes that could subsequently contribute to physical disability. However, whether and to what extent air pollution exposure is associated with objective measures of physical functioning remains understudied. Methods: We used longitudinal data from the China Health and Retirement Longitudinal Study (CHARLS) and included 10 823 participants who were surveyed at least twice. Annual average exposure to fine particulate matter (PM2.5 ) was assessed using a state-of-the-art estimator. Physical functioning was assessed with 4 objective tests covering hand-grip strength, balance, repeated chair stands, and gait speed. Mixed-effects models with participants as a random term were used to estimate associations with multiple adjustments. Results: We found a significant and robust association between exposure to increased PM2.5 and the reduction in hand-grip strength and balance ability. Each 10 μg/m 3 increase in annual averaged concentrations of PM2.5 was associated with a 220-g (95% confidence interval [CI]: 127, 312 g) reduction in hand-grip strength per 60 kg of body weight and a 5% risk (95% CI: 2, 7) of reduced balance ability. The estimated effect of each 10 μg/m 3 increase in PM2.5 on hand-grip strength and balance ability was equivalent to the effect of aging (1.12 [95% CI: 0.76, 1.48] and 0.98 [95% CI: 0.50, 1.50] years, respectively). Conclusions: PM2.5 may be differentially associated with various dimensions of physical functioning. Improving air quality can prevent physical disability.